The effect of Nano-MgO on the mechanical and flammability properties of hybrid nano composites from wood flour-polyethylene - Kiaei, Majid; Rastegar Moghdam, Yaser; Kord, Behzad; Samariha, Ahmad (Maderas. Ciencia y Tecnología, 2017)
This study considered the effect of nanomagnesium oxide on the mechanical and flammability features of composites made of wood flour and high-density polyethylene. A sample of wood flour was made from the mixture of hardwoods and high density polyethylene with the weight ratio of 50%. Maleic anhydride was added as a compatibilizer (2 phc), and nanomagnesium oxide was applied at 6 levels (0, 1, 2, 3, 4, 5 phc). These materials were mixed, and samples were prepared with determined sizes by injection molding machine. The samples were subjected to flexural tests to examine the mechanical features, and to study flammability strength, various tests were conducted with a cone calorimeter, including the amount of char residue, total smoke production, time to ignition, and heat release rate, according to ASTM E1354-92 (1992). The addition of up to 3 phc nanomagnesium oxide increased flexural strength and modulus, but further additions decreased these values. The addition of 5 phc nanomagnesium oxide increased the char residue and ignition time, and it decreased the heat release rate, total smoke production, and burning rate. Scanning electron microscopy and energy dispersive X-ray (EDX) analysis indicated the improper transmittance of nanomagnesium oxide and accumulations in the samples. PDF XML